Genetic variation in the Medicago sativa complex - Julier B.; Huyghe C.; Guy P.; Crochemore M.L. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
Historically, theoretical and experimental studies were developed on quantitative genetic, of tetraploids, based on lucerne. Genetic variation for agronomic, morphological, biochemical and molecular traits is under study. Results are presented on the variation within the Medicago sativa complex for such traits. Using agronomic and morphological traits with Principal Component Analysis, two groups of populations were separated, the first one with all the tetraploid, cultivated populations from the subspecies sativa, the second one with all the wild populations, diploid or tetraploid, from both subspecies sativa and falcata. The content in medicagenic acid, part of the main anti-nutritional saponin, is much lower in the pure sativa populations than in the falcata populations, and the sativa populations hybridised with falcata types had intermediate level. The lab is now focused on nutritive value of lucerne. It appears that stem digestibility, relatively to dry matter yield, is higher in wild than in cultivated populations. Molecular markers such as RAPD were used to study the relationships between populations. The approach developed here was based on population specific bands, so each population was represented by the mixed DNA of 30 individuals. Genetic distances were calculated, and trees drawn. The distinction between the populations from the two subspecies sativa and falcata was clear. However, the classification within the sativa subspecies was not related to the genetic origins or the agronomic characters of the populations. However, this study shows that RAPD markers could be used in variety distinction, as specific bands were found.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)